Antioxidant of Ethanol Extract and Toxicity of Fractions from Aspergillus unguis a Marine Sponge Symbiont of Aaptos suberitoides - Masyerli, Scify Bilqis Nawafi; Efdi, Mai; Bashari, Muhammad Hasan; Untung Kurnia Agung, Mochamad; Subhan, Beginer; Efahmi, Efahmi; Andriani, Yosie; Syafrizayanti, Syafrizayanti (Hydrogen: Jurnal Kependidikan Kimia, 2025)
The marine sponge Aaptos suberitoides has been shown to have anticancer properties, with clear evidence of its capacity to suppress the growth of cancer cells. However, the pharmaceutical exploration of chemicals from marine organisms causes significant environmental concerns. Aspergillus unguis, a fungal symbiont of the marine sponge A. suberitoides, has been isolated for its potential in sustainable natural products resources. This study assesses the antioxidant activity of ethanol extract and the toxicity of four levels fractions from ethanol extracts of A. unguis mycelium and these results were reported for the first time in this study. The antioxidant of ethanol extract was determined using the 2,2-Diphenyl-1-picrylhydrazyl (DPPH) method. The fractions were examined for toxicity using the Brine Shrimp Lethality Test (BSLT). The ethanol extract of A. unguis shows very strong antioxidant bioactivity (IC50 = 42.84 mg/L). The LC50 values for hexane, chloroform, ethyl acetate, and butanol fractions were determined to be 74.11 µg/mL, 93.84 µg/mL, 59.37 µg/mL, and 142.79 µg/mL, respectively. It indicates significant toxicity. These preliminary results are important knowledge for further research into the bioactivity potential of the metabolites as candidate anticancer compounds, aligning with marine pharmaceutical drug development.